PEMANFAATAN NASI BASI SEBAGAI PUPUK ORGANIK CAIR DAN APLIKASINYA UNTUK PEMUPUKAN TANAMAN BUNGA KERTAS ORANGE (Bougainvillea spectabilis) - Sriyundiyati, Ni Putu; Supriadi, Supriadi; Nuryanti, Siti (Universitas Tadulako, 2013)
Stale rice is the production result of inapproprite food to consume due to have bad smell and taste, mucus appearance, grown with yellow or orange fungus and sour taste because microorganism living in it. It is only throw by the household as the waste. Thus, it needs a process that it becomes useful and quality product. One of the product is the making of liquid organic fertilizer (POC). This study aims to create a POC and determine the amount of nitrogen in the POC. The research method is the preparation of stale rice, followed manufacture of POC through fermentation and determination of N-Total with destruction. POC later applied for fertilization in plants of orange paper flower (bougainvillea spectabilis), then performed observations shoot height of plants , leaves number, leaves shape, leaves colour , flowers number and the analysis of one of ingredients N-total POC in stale rice. N-total in POC of stale rice obtained wet destruction method as much as 92 mg/L (92 ppm). The liquid organic fertilizer from stale rice can accelerate the growth of orange paper flowers (Bougainvillea spectabilis) is indicated by the number of shoots, leaves and flower petals.